Pettazzoni, Leland e gli Etruschi - Capdeville, Gérard (Studi e materiali di storia delle religioni, 2011)
In 1892, the American Charles Godfrey Leland, known until then as a folklorist specialized in the Tsiganes and the Algonchins Indians, published in London a book entitled Etruscan Roman Remains in Popular Tradition, the result of an extensive investigation in the Romagna Toscana: by means of local informants, Leland had collected traditions and folk songs, that held memories of the old Etruscan deities, with names barely altered: Tigna, Turanna, Faflon … At that time, the book went almost unnoticed in Italy, with only same sporadic reports rather positive, even if doubtful on the validity of the method. It reappeared at the moment of the First International Etruscan Congress (Florence 1928), when it was quoted by Raffaele Pettazzoni - apropos of the survival of Tinia - with the proposal of holding an inquiry in the field in order to verify and to complete the work of Leland. That gave rise to a sharp polemic, led by Raffaele Corso, »for the honour of the Italian science» (and of same scholars humiliated to see an Italian community treated as an Indian tribe). The inquiry didn't take place. A reprint of the book in 1963 caused a new burst, not yet exhausted, of violent critiques, with the contribution of foreign scholars, like Hendrik Wagenvoort and Raymond Bloch. On the contrary the very scientific behaviour of Pettazzoni was imitated by Ambros Joseph Pfiffig in a long development in conclusion of his Religio Etrusca (Graz 1975) and by Giovannangelo Camporeale, who quotes even an excerpt of the song to Faflon in his handbook on Gli Etruschi (Turin 2000). Unfortunatly the informants have now disappeared since a long time and with them probably all what seemed to survive from the Etruscan legacy until the last years of the XIX century.